El control interno y su influencia en la administración de las cuentas por pagar en la Empresa MOISOLMOON S.A. - Ronquillo Olivo, Melissa Solange (2024)
This research work results from the existence of certain companies that do not take into account correct management procedures in their operations and in most cases operate on the basis of experience, therefore, internal control is the main factor to achieve proper corporate management as it provides confidence in achieving the objectives set, so the overall objective of this study is to examine the influence of internal control in the management of accounts payable in the company MOISOLMOON SA. The MOISOLMOON company has problems with incorrect and late records in the accounting department and in the financial area, improper payments to suppliers and credit losses, which generates discomfort within the company. In the accounts payable area, an inadequate internal control management by the managers is determined. Throughout this research process, research is carried out on theoretical bases which provide content that encompasses internal control such as COSO components, as well as the procedures to be followed in accounts payable. In relation to the methodology used, a mixed qualitative and quantitative approach is considered. The scope of the research is a descriptive study. By means of the techniques and instruments of the research, data collection is carried out through internal control questionnaires with the objective of analyzing the real situation of the company. Consequently, the documentary analysis where financial ratios are made: indebtedness, liquidity and accounts payable turnover, which facilitates to describe the impact that occurs in this item due to a deficient control in the internal ones. Finally, a technical report is made where the results obtained from this research are reported, in addition to providing guidelines to follow on a correct internal control in accounts payable, in order to obtain convenient results for the organization.